ENVIRONMENTAL DIPLOMACY: CASE STUDY OF THE EU-INDONESIA PALM OIL DISPUTE - Robertua, Verdinand , (Jurnal Mandala, 2019)
The EU’s decision to exclude palm oil as renewable energy in the Renewable Energy Directive II (RED) faced critics and protest from Indonesia and Malaysia. However, the EU argued that the expansion of palm oil has direct link with deforestation and degradation of forest. This research is eager to understand the dynamic of the European Union environmental diplomacy in the case study of the EU-Indonesia palm oil dispute. This research found that the dynamic of the EU environmental diplomacy in the case study of the EU-Indonesia palm oil dispute has three phases namely the low-carbon economy, the EU green leadership and the EU-Indonesia trade war.